Genetic Testing Distinguishes Multiple Chondroid Chordomas with Neuraxial Bone Metastases from Multicentric Tumors. (29th November 2020) - Kobayashi, Hiroshi; Shin, Masahiro; Makise, Naohiro; Shinozaki-Ushiku, Aya; Ikegami, Masachika; Taniguchi, Yuki; Shinoda, Yusuke; Kohsaka, Shinji; Ushiku, Tetsuo; Oda, Katsutoshi; Miyagawa, Kiyoshi; Aburatani, Hiroyuki; et al.
Abstract : Background . Chordomas are rare malignant bone tumors preferentially forming in neuraxial bones. Chondroid chordoma is a subtype of chordoma. Chordomas reportedly present as synchronous multiple lesions upon initial diagnosis. However, it remains unknown whether these lesions are multicentric or metastatic multiple chordoma tumors. Case Presentation . Here, we present the case of a 57-year-old woman with multiple chordomas at the clivus, C6, and T12 upon initial presentation. Sequential surgeries and radiotherapy were performed for these lesions, and postoperative histological diagnosis revealed that all lesions were chondroid chordomas. Next-generation sequencing revealed that these lesions harbored a common somatic mutation in epidermal growth factor receptor ( EGFR ), c.3617A>C, which is not considered a pathogenic chordoma mutation, thus indicating that these lesions were not multicentric but rather multiple metastatic tumors. Subsequent multiple metastases to the lung and appendicular and axial bones were detected 15 months after the initial surgery. Recurrent lesions at the clivus progressed despite EGFR-targeted therapy, surgery, and radiotherapy. Conclusion . The present evidence indicates that multiple chordomas in this case were caused by multiple metastases rather than multicentric lesions. Multiple presentations of chordoma imply systemic dissemination of tumor cells, and novel efficient systemic therapy is required to treat this disease.